e-Governance in Local Governments: Aiming Towards Good Governance - Sabu Thomas (KILA Journal of Local Governance, 2014)
The use of Information and Communica- tion Technology (ICT) is a major innovation of modern governance systems. It is argued that the introduction of ICT in governance provided for a participant and vibrant democratic culture. It follows that the digital culture automatically retains its foot prints in the local governance environment. Thus local governance is facing a digital transformation. The necessity of transformation being accredited, the imminent issue is the implementation and management of these transition. In this background the paper examines the use of e-Governance in local government and its implications in the decentralization process in the state of Kerala.